2019
DOI: 10.21873/invivo.11782
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA Methylation Profiling of Blood from Monozygotic Twins Discordant for Myocardial Infarction

Abstract: Background/Aim: This study aimed to measure the DNA methylation state of thousands of CpG islands in the blood of two monozygotic twins that were discordant for cardiovascular disease (CVD). Twin 1 had suffered myocardial infarction, while the other was healthy. Patients and Methods: Since the aim of this study was to identify differentially methylated regions which might act as potential markers, reduced-representation bisulfite libraries were used for whole-genome methylation analysis. Results: According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Cao et al reported that ACSM5 was low expressed in renal tissue of rats with chronic glomerulonephritis (CGN), while Qiteng Xiaozhao granules significantly increased the low expression of ACSM5 in the renal tissue of rats with CGN, suggesting that ACSM5 was involved in the occurrence and development of CGN [ 44 ]. Cao et al found that ACSM5 gene was hypermethylated in the peripheral blood of patients with myocardial infarction, and its methylation site and level might be closely related to the occurrence of myocardial infarction [ 45 ]. However, the role of ACSM5 in the HLF has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al reported that ACSM5 was low expressed in renal tissue of rats with chronic glomerulonephritis (CGN), while Qiteng Xiaozhao granules significantly increased the low expression of ACSM5 in the renal tissue of rats with CGN, suggesting that ACSM5 was involved in the occurrence and development of CGN [ 44 ]. Cao et al found that ACSM5 gene was hypermethylated in the peripheral blood of patients with myocardial infarction, and its methylation site and level might be closely related to the occurrence of myocardial infarction [ 45 ]. However, the role of ACSM5 in the HLF has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…These CpGs sites and genes stress the correlation of ion regulation, lipid metabolism, and inflammation in the MI biological mechanisms (Fernández-Sanlés et al, 2021). Thus, the new DNA methylation sequencing technology can identify potential target sites related to the aberrant epigenetic regulation of MI (Koseler et al, 2020). Additionally, the sites stated by two studies (Guarrera et al, 2015;Nakatochi et al, 2017) are candidates for further assessment as underlying MI biomarkers.…”
Section: Dna Methylation and MImentioning
confidence: 97%
“…Hypomethylation of the IL6 gene promoter is also associated with this nosology [32]. The study of 27-year-old monozygotic male twins discordant for myocardial infarction showed hypomethylation of the LDAH, APOB, ACSM2A, ACSM5, ACSF3, CES1, CES1P1, AFG3L2, ISCU, SEC14L2, MTTP genes in a twin without myocardial infarction (twins have the same work and have no risk factors associated with pathology) [71].…”
Section: Dna Methylation and Ischemic Heart Diseasementioning
confidence: 99%